Down but not out: Exploring the barriers of employment for Persons with Down syndrome from the Malaysian perspectives - Md Mizanur, Rahman; Abg Safuan, Adenan; Sharifa Ezat, Wan Puteh; Razitasham, Safii; Rosalia, Saimon; Chen, Yoke Yong; Ting, Chuong Hock (Azerbaijan Medical Journal, 2022)
Globally, individuals with disabilities have a notably higher unemployment rate. The socioeconomic research on individuals with Down syndrome in Malaysia is scant, as no current data on their employment exist, and the reasons for these low employment rates are not understood. With the utmost need to uphold their employment rights, this study aims to explore the employment barriers of individuals with Down syndrome in Malaysia from multiple perspectives. A series of online semi-structured interviews were conducted. In total, 45 participants, including six individuals with Down syndrome, ten family members, six employers and co-workers, 22 community members, and one policymaker were interviewed. A reflexive thematic analysis was employed to generate a thematic concept on the barriers of employment. Five themes were generated to explain the employment barriers for individuals with Down syndrome: (1) “in the end, it’s they themselves”: individual circumstances; (2) “would their family support them?”: family concerns; (3) “employers are hesitant to change”: organisational practice; (4) “some people shy away from them”: social norm; and (5) “there’s not enough room to grow”: restrictive environment. Barriers to employment for individuals with Down syndrome are complex issues interwoven within every aspect of our social and environmental context. Therefore, securing employment is not only individualistic but demands the willingness of society and the workforce to accommodate them. Relevant authorities, non-governmental organisations, and private sectors can utilise the findings to develop employment policies.